A comparative study of human and zebrafish glucocorticoid receptor activities of natural and pharmaceutical steroids - Toso, Anna; Boulahtouf, Abdelhay; Escande, Aurélie; Garoche, Clémentine; Balaguer, Patrick (Frontiers in Endocrinology, 2023)
Introduction The action of environmental steroids on the human glucocorticoid receptor (hGR) has been pointed out with the risk to impair physiological immune and metabolic processes regulated by this nuclear receptor. However, there is still a lack of mechanistic information regarding their ability to interact with GR in aquatic species. Methods To investigate ligand activation differences between hGR and zebrafish GR (zfGR), we tested several natural and synthetic steroids using reporter cell lines expressing hGR or zfGR. Results and discussion Almost all the glucocorticoids tested (dexamethasone, cortisol, bimedrazol, medrol, cortivazol and fluticasone) are agonists of the two receptors with similar potencies. The dissociated glucocorticoids, RU24782 and RU24858 are agonists of both zfGR and hGR but with a better potency for the latter. On the other hand, the synthetic glucocorticoid forbimenol and the mineralocorticoid aldosterone are agonist on hGR but antagonist on zfGR. The other steroids tested, androgens and progestins, are all antagonists of both GRs with equal or lower potency on zfGR than on hGR. Surprisingly, the lower efficacy and potency on zfGR of aldosterone, forbimenol and the dissociated glucocorticoids is not related to their affinity for the receptors which would suggest that it could be related to less efficacious recruitment of coactivators by zfGR compared to hGR.